2010
DOI: 10.1525/mp.2010.27.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Music-Supported Training is More Efficient than Functional Motor Training for Recovery of Fine Motor Skills in Stroke Patients

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.University of California Press is collaborating with JSTOR to digitize, preserve and extend access to Music Perception: An Interdisciplinary Journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 25 publications
3
98
0
Order By: Relevance
“…Along with fine motor recovery, an increase in neuronal connectivity between sensorimotor and auditory regions was demonstrated by means of electroencephalograph-coherence measures. [41][42][43] Therefore, establishing an audio-sensorimotor co-representation may support the rehabilitation process (see Figure 1). This notion is corroborated by findings in a patient who underwent musicsupported training 20 months after a stroke.…”
Section: Music-supported Motor Therapy In Patients With Strokementioning
confidence: 99%
“…Along with fine motor recovery, an increase in neuronal connectivity between sensorimotor and auditory regions was demonstrated by means of electroencephalograph-coherence measures. [41][42][43] Therefore, establishing an audio-sensorimotor co-representation may support the rehabilitation process (see Figure 1). This notion is corroborated by findings in a patient who underwent musicsupported training 20 months after a stroke.…”
Section: Music-supported Motor Therapy In Patients With Strokementioning
confidence: 99%
“…We focused on their category of ''stimulus,'' identifying studies using isolated sounds and/or sequential sounds (n ¼ 120). We omitted one article involving sound production rather than perception (Schneider, Mü nte, Rodriguez-Fornells, Sailer, & Altenmü ller, 2010) and another primarily reviewing previously published data (D 'Amato, 1988) A third article included separate visual and auditory experiments (Breckler, Allen, & Konecni, 1985); and so we included the auditory but omitted the visual. Therefore, our final corpus consisted of 118 empirical papers identified by Tirovolas & Levitin, (2011) as those using single tones or a series of tones.…”
Section: Identifying the Corpus Of Sounds To Surveymentioning
confidence: 99%
“…Schneider et al 12 13 showed that music therapy can improve speed, precision, and smoothness of fine and gross motor skills in patients with stroke. Auditory stimulation can also enhance gait ability, flexibility and upper limb motor performance in patients with stroke 14–18.…”
Section: Introductionmentioning
confidence: 99%